IMF Staff papers : Volume 14 No. 1. (IMF Staff Papers; IMF Staff Papers, 1967)
This paper reviews developments in the flow of private capital during 1957-1965 within the limitations of the basic data. This paper is divided into five sections. The paper examines the statistics on a broad global basis to gauge the rough magnitude of flows between the industrial and nonindustrial countries, analysed between long-term and short-term capital. The published figures show a net inflow of short-term capital to the nonindustrial countries over the two four-year periods, but the large negative net errors and omissions item for these countries suggests that some capital outflows have passed unidentified. The pattern of growth in direct investment from the first to the second four-year period suggests a decrease in the flow to the nonindustrial countries as a group. Despite the change in direct investment in nonindustrial countries shown by the aggregate figures, all the areas, except Latin America, registered appreciably greater direct investment receipts in the second than in the first four-year period.